Analisis Modal Manusia, Investasi, dan Teknologi terhadap Pertumbuhan Ekonomi Sumatera Barat - Azizah Putri Wulandari; Ariusni Ariusni (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2022)
This study aims to identify and analyze. (1) What is the impact of labor on theeconomic growth of West Sumatra? (2) What is the impact of human capital onthe economic growth of West Sumatra? (3) What is the impact of investment onthe economic growth of West Sumatra? (4) What is the impact of technology onthe economic growth of West Sumatra, and (5) What is the impact of labor,human capital, investment, and technology on the economic growth of WestSumatra? This study is descriptive and inductive using panel data regressionanalysis using a random-effects model (REM) method using time series 2017-2020 taken from 19 district/city across province from related agencies in WestSumatra.The results show that the effects of labor, human capital, investment, andtechnology at the same time had a significant positive impact on WestSumatra's economic growth. In addition, in part, (1) labor has negative andslightly impact on West Sumatra's economic growth, (2) human capital has apositive and significant impact on West Sumatra's economic growth, and (3)investment study on economic growth in West Sumatra that has a positive andslightly impact. West Sumatra. West Sumatra, (4) Technology has a negativeand significant impact on West Sumatra's economic growth. Therefore, labor,human capital, investment, and technology are the most important aspects ofWest Sumatra's economic growth.